Modern air-launched weapons - Dougherty, Martin J. (Amber Books, 2019)
An extensively researched and comprehensively illustrated guide to air-launched weapons and their use in combat. Features more than 300 specially commissioned computer-generated illustrations of weapons, loadouts and aircraft. Explains the use of each weapon and how weapons are combined on an aircraft's airframe for maximum efficiency. Includes an extensive directory of missiles, bombs and pods with full technical specifications and three-view diagrams.